2015
DOI: 10.1128/mcb.00985-14
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Gene Expression via Liver X Receptor α Serine 198 Phosphorylation

Abstract: e In mouse models of atherosclerosis, normalization of hyperlipidemia promotes macrophage emigration and regression of atherosclerotic plaques in part by liver X receptor (LXR)-mediated induction of the chemokine receptor CCR7. Here we report that LXR␣ serine 198 (S198) phosphorylation modulates CCR7 expression. Low levels of S198 phosphorylation are observed in plaque macrophages in the regression environment where high levels of CCR7 expression are observed. Consistent with these findings, CCR7 gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…Whereas LXRa pS196 promotes an inflammatory gene signature, unphosphorylated LXRa stimulates an anti-inflammatory gene expression profile. Consistent with this idea, in mouse models we observed an increase in LXRa pS196 in plaque macrophages under inflammatory conditions associated with atherosclerosis progression, and a decrease in LXRa pS196 during the resolution of inflammation in regressing plaques (16,18). Cholesterol loaded macrophages and hepatocytes also showed increased LXRa pS196 (15,19).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Whereas LXRa pS196 promotes an inflammatory gene signature, unphosphorylated LXRa stimulates an anti-inflammatory gene expression profile. Consistent with this idea, in mouse models we observed an increase in LXRa pS196 in plaque macrophages under inflammatory conditions associated with atherosclerosis progression, and a decrease in LXRa pS196 during the resolution of inflammation in regressing plaques (16,18). Cholesterol loaded macrophages and hepatocytes also showed increased LXRa pS196 (15,19).…”
Section: Introductionsupporting
confidence: 83%
“…We and others have shown that LXRa's ability to activate transcription is modulated by phosphorylation at serine 196 (S196 in mouse LXRa and S198 in human LXRa), which significantly modifies its target gene repertoire (14)(15)(16)(17). Whereas LXRa pS196 promotes an inflammatory gene signature, unphosphorylated LXRa stimulates an anti-inflammatory gene expression profile.…”
Section: Introductionmentioning
confidence: 99%
“…119 On reversal of hypercholesterolemia or treatment with statins, the induction of CCR7 in plaque macrophages may promote plaque regression. [120][121][122][123][124][125] Collectively these data suggest that monocyte recruitment and macrophage proliferation, but not macrophage egress, are the key cellular events regulating foam cell lesion progression.…”
Section: Macrophage Proliferation and Dynamics In Atherosclerotic Lesmentioning
confidence: 85%
“…Instead of directly interacting with its target genes, ligand-induced SUMOyLation of LXR allows it to bind to co-repressor complexes, preventing their release and the subsequent transcription of pro-inflammatory target genes of the transcription factors NF-K B and activator protein 1 (AP-1) [17]. Interestingly, we also reported that LXR phosphorylation affects corepressor interactions and chromatin modifications in regulatory sites of target genes [18,19].…”
Section: Responses To Inflammatory Stimulimentioning
confidence: 85%